Improved growth and nutrient acquisition of wheat genotypes in phosphorus deficient soils by plant growth-promoting rhizospheric and endophytic bacteria. Issue 6 (2nd November 2018) - Emami, Somayeh; Alikhani, Hossein Ali; Pourbabaei, Ahmad Ali; Etesami, Hassan; Motashare Zadeh, Babak; Sarmadian, Fereydoon
ABSTRACT: In this study, two bacterial strains were isolated from the rhizosphere and inside the roots of wheat ( Triticum aestivum L.) plants growing in wheat land of Iran. Based on the 16s rRNA gene sequences, strains R185 and E240 were identified as Pseudomonas sp. (rhizospheric isolate) and Pseudomonas mosselii (endophytic isolate), respectively. Isolates were tested for traits that affect plant growth such as indole-3-acetic acid, siderophore, hydrogen cyanide production, and phosphate solubilization ability. Then the effect of strains on growth promotion, protein, nutrients of grains, and soil enzyme activity was investigated using a low-phosphorous soil under greenhouse conditions. Results revealed that significantly higher biomass accumulation and micronutrient assimilation were obtained in all the pots treated with bacterial strains as compared to the control. Co-inoculation of rhizospheric and endophytic bacteria improved the protein of grain by 11.3% ( Marvdasht ) and 9% ( Roshan ). Microbial inoculation had a positive effect on the concentration of P, Zn, and Fe in wheat grains. While inoculating wheat genotypes with a single rhizospheric strain increased dehydrogenase activity by 53.4%, this effect became stronger with increasing endophytic strain: up to 72% increase in soil dehydrogenase activity was observed in bacterial consortium treatment. Taken together, inoculation by rhizospheric–endophytic mix-strains with multi-plant growth-promoting traits could be a promising option to promote cereal quality.